PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF FLIPBOOK PADA MATA PELAJARAN PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV SD - Ridiyanto, Ridiyanto; Sutrisna Wibawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the motivation of students in learning Pancasila Education which is still low and they are less active in implementing learning. The aim of the development carried out by the researcher is to produce interactive learning media, flipbook, material for flat construction for fourth grade elementary school students, seen from its validity, attractiveness and practicality. This research includes research and development (Research and Development), using the ADDIE research model from the Analyze, Design, Develop, Implement, and Evaluate stages which go through several stages, namely analysis, design, development, implementation, and evaluation. The trial of interactive learning media was supported by an expert team validity assessment, and validity questionnaire data from fourth grade elementary school student respondents, and based on the results of the material expert's assessment, they got a score of 82% in the very feasible and valid category, media experts got a score of 83% in the category very feasible and interesting, and the small scale assessment of 7 respondents from students averaged 4.65 in the very practical category, so it can be concluded that this flipbook interactive media is suitable for use by students.